2015
DOI: 10.1016/j.neulet.2015.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Activation of cannabinoid receptor 1 inhibits increased bladder activity induced by nerve growth factor

Abstract: Nerve growth factor (NGF) is an important mediator of inflammatory pain, in part by sensitizing afferent nerve fibers, and expression of NGF is increased during bladder inflammation. We investigated whether intravesical instillation of the selective cannabinoid receptor 1 (CB1) agonist arachidonyl-2'-chloroethylamide (ACEA) affects NGF-induced increased bladder activity in female C57BL/6J wild-type (WT) mice. We also examined the effects of intravesical NGF in female fatty acid amide hydrolase knock-out (FAAH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Systemically administered cannabinoids can act at multiple sites, including the bladder and many sites in the central nerve system. Intravesical activation of CB1 does block Nerve Growth Factor-induced increased bladder activity [ 17 ]. In addition, according to Tyagi et al, CB1 and CB2 receptors have higher expression rates in the bladder urothelium, and bladder strips incubated for 15 min CB agonists show a decreased detrusor muscle contraction amplitude [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Systemically administered cannabinoids can act at multiple sites, including the bladder and many sites in the central nerve system. Intravesical activation of CB1 does block Nerve Growth Factor-induced increased bladder activity [ 17 ]. In addition, according to Tyagi et al, CB1 and CB2 receptors have higher expression rates in the bladder urothelium, and bladder strips incubated for 15 min CB agonists show a decreased detrusor muscle contraction amplitude [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Afferent nerve activity was recorded during increasing intravesical pressure in inflamed bladders ex vivo in the presence or absence of intravesical cannabinoid agonists, and it was determined that intravesical cannabinoids suppressed afferent nerve fiber firing in inflamed bladders via CB1 activation (Walczak et al, 2009 ; Walczak and Cervero, 2011 ). We have also observed that intravesical administration of a CB1 agonist inhibited bladder responses to subsequent instillation of NGF (Wang et al, 2015a ). These studies support the concept that intravesical manipulation of the endocannabinoid system may have the capacity to alter nociceptive signaling.…”
Section: Endocannabinoids and Bladder Painmentioning
confidence: 74%
“…A majority of somatic and visceral afferent nerve fibers express CB1 (Hohmann and Herkenham, 1999 ; Ahluwalia et al, 2000 ; Agarwal et al, 2007 ), and genetic deletion of CB1 from afferent nerves renders mice sensitive to subthreshold stimuli (allodynia) and enhances response to noxious stimuli (hyperalgesia; Agarwal et al, 2007 ). We demonstrated that CB1 receptors have the capacity to suppress the sensitizing effect of nerve growth factor (NGF) on the response of mouse afferent neurons to capsaicin in vitro (Wang et al, 2015a ). Interestingly, we also showed that intrathecal administration of the CB1 agonist arachidonyl-2’-chloroethylamide (ACEA) blocked referred mechanical hypersensitivity induced by inflammatory cystitis in rats (Jones et al, 2015 ).…”
Section: Cannabinoid Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Supporting this suggestion, a recent report by Wang et al. shows that intravesical application of a CB 1 agonist decreases bladder overactivity induced by intravesical nerve growth factor (NGF) in mice with an intact urothelial layer. Additionally, NGF did not induce bladder overactivity in knockout mice for the FAAH enzyme, reinforcing the suggestion for Aizawa et al.…”
mentioning
confidence: 87%